Fracture characterization in tubular LSFCO ceramic membranes - Nagendra, N.; Klie, R.F.; Browning, N.D.; Bandhopadhyay, S. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2003)
Lanthanum based perovskite oxides are subject of extensive studies for application as oxygen-separation membranes where they are designed to be used as tubes in advanced reactors. In the present study, tubular La 0.2Sr 0.8Fe 0.8Cr 0.2O 3− δ perovskite membrane has been evaluated for structural properties viz. fracture strength in two different conditions: ambient and in N 2 at 1000 °C and 0.17 MPa. The results show that in the slightly reducing condition, the fracture strength of the perovskite tubes decrease to nearly half its value at ambient conditions (186 and 307 MPa, respectively) with a negligible change in the Weibull modulus ( m). The fracture origins are primarily processing related surface and volume flaws. Microscopic analysis indicates that fracture is brittle and by transgranular cleavage. In reducing conditions, there is a drastic change in fracture morphology and can be argued as being aided by creation of excess oxygen defects in the membrane. A strong correlation is observed to exist between the fracture strength, fracture morphology and defect chemistry in a tubular LSFCO membrane.